As representações sociais do trabalho entre um grupo de praticantes de ginástica laboral: um estudo de caso do Centro Universitário FEEVALE - Konrath, Magale (Universidade do Vale do Rio do Sinos, 2006)
This study investigates the Labor Representations among the participants of the Labor Gymnastics group at Centro Universitário Feevale, and it aims at identifying how the Social Representations of Work manifest among the participants, in a study case. The methodology adopted is based on the Comprehensive Sociology (WEBER, 1999), within the qualitative research paradigm, and reading and interpreting data is made through phenomenology (SCHÜTZ, in MYNAYO, 2000). The researched group was composed by 8 (eight) female employees from the Cleaning Sector and the tools used for data collection were semi-structured interviews, focal group, participant observation and the field diary. The theoretical references mentioned: labor and its productive restructuration, where the centrality of work is discussed (ANTUNES, 2002 and 2003; POCHMANN, 2001) and the finality of work (GORZ, 1988, 2003 and 2004; OFFE, 1989, 1991); the Social Representations (MOSCOVICI, 2004), where a little of this recent theory is explained; and the
Keywords: qualidade de vida; trabalho; ginástica laboral; representações sociais; saúde; health; labor gymnastics; life quality; social representations; work; labor; Ciências Humanas